Phosphodiesterase-5 inhibitor sildenafil attenuates kidney injury induced by Bothrops alternatus snake venom. (30th October 2021) - Jorge, Antônio Rafael Coelho; Marinho, Aline Diogo; Silveira, João Alison de Moraes; Nogueira Junior, Francisco Assis; de Aquino, Pedro Everson Alexandre; Alves, Ana Paula Negreiros Nunes; Jorge, Roberta Jeane Bezerra; Ferreira Junior, Rui Seabra; Monteiro, Helena Serra Azul
Abstract: Acute kidney injury pathogenesis in envenoming by snakes is multifactorial and involves immunologic reactions, hemodynamic disturbances, and direct nephrotoxicity. Sildenafil (SFC), a phosphodiesterase 5 inhibitor, has been reported to protect against pathological kidney changes. Objective: This study aimed to investigate the protective effect of sildenafil against Bothrops alternatus snake venom ( Ba V)-induced nephrotoxicity. Methods: Kidneys from Wistar rats (n = 6, weighing 260–300 g) were isolated and divided into four groups: (1) perfused with a modified Krebs-Henseleit solution (MKHS) containing 6 g% of bovine serum albumin; (2) administered 3 μg/mL SFC; (3) perfused with 3 μg/mL Ba V; and (4) administered SFC +  Ba V, both at 3 μg/mL. Subsequently, the perfusion pressure (PP), renal vascular resistance (RVR), urinary flow (UF), glomerular filtration rate (GFR), and percentage of electrolyte tubular sodium and chloride transport (%TNa +, %TCl −, respectively) were evaluated. The cyclic guanosine monophosphate (cGMP) levels were analyzed in the perfusate, and the kidneys were removed to perform oxidative stress and histopathological analyses. Results: All renal parameters evaluated were reduced with Ba V. In the SFC +  Ba V group, SFC restored PP to normal values and promoted a significant increase in %TNa + and %TCl − . cGMP levels were increased in the SFC +  Ba V group. The oxidative stress biomarkers, malondialdehyde (MDA) and glutathione (GSH), were reduced by Ba V. In the SFC +  Ba V group, a decrease in MDA without an increase in GSH was observed. These findings were confirmed by histological analysis, which showed improvement mainly in tubulis. Conclusion: Our data suggest the involvement of phosphodiesterase-5 and cGMP in Ba V-induced nephrotoxicity since its effects were attenuated by the administration of SFC. Highlights: Sildenafil (SFC) protects kidney against B. alternatus snake venom ( Ba V) effects. SFC reversed vascular and functional alterations induced by Ba V. SFC reduced lipid peroxidation caused by Ba V. SFC improved histological alterations induced by Ba V. SFC further enhanced Ba V-induced increase in cGMP kidney levels.